Longitudinal trajectories of posttraumatic headache after pediatric mild traumatic brain injury. (May 2023) - Marbil, Mica Gabrielle; Ware, Ashley L; Galarneau, Jean-Michel; Minich, Nori Mercuri; Hershey, Andrew D; Orr, Serena L; Defta, Dana M; Taylor, H Gerry; Bigler, Erin D; Cohen, Daniel M; Mihalov, Leslie K; Bacevice, Ann; et al.
Objective: This prospective, longitudinal cohort study examined the trajectory, classification, and features of posttraumatic headache after pediatric mild traumatic brain injury. Methods: Children ( N  = 213; ages 8.00 to 16.99 years) were recruited from two pediatric emergency departments <24 hours of sustaining a mild traumatic brain injury or mild orthopedic injury. At 10 days, three months, and six months postinjury, parents completed a standardized questionnaire that was used to classify premorbid and posttraumatic headache as migraine, tension-type headache, or not otherwise classified. Multilevel mixed effects models were used to examine posttraumatic headache rate, severity, frequency, and duration in relation to group, time postinjury, and premorbid headache, controlling for age, sex, and site. Results: PTH risk was greater after mild traumatic brain injury than mild orthopedic injury at 10 days (odds ratio = 197.41, p  < .001) and three months postinjury (odds ratio = 3.50, p  = .030), especially in children without premorbid headache. Posttraumatic headache was more frequent after mild traumatic brain injury than mild orthopedic injury, β (95% confidence interval) = 0.80 (0.05, 1.55). Groups did not differ in other examined headache features and classification any time postinjury. Conclusions: Posttraumatic headache risk increases after mild traumatic brain injury relative to mild orthopedic injury for approximately three months postinjury, but is not clearly associated with a distinct phenotype.